Social patterns of energy usage: An international comparison. (December 2017) - Patiño, Rodrigo; Goupil, Christophe
Abstract: In order to reduce the enormous environmental footprint of the contemporary society, it would be necessary to diminish the energy wastes in human activities. To tackle these objectives, it is important to identify the sources of this reduction from the point of view of both technical systems and social practices. With this perspective, an analysis of the social patterns of energy usage is presented in this work for a number of different regions among the five continents. As a first approach, this study is mainly based on the official data found from international organisms. The urbanization rate for every region is considered here as the central point of a model at three different scales: (i) the World, (ii) subcontinents or groups of countries, and (iii) single countries. With this methodology, it is possible to classify a number of patterns of social energy consumption and its evolution with time for the last two decades. A transition point is regarded for a number of regions, while stability or instability is found for others regions.